A structural VAR model of the New Zealand business cycle - Robert A Buckle; Kunhong Kim; Heather Kirkham; Nathan McLellan; Jared Sharma (New Zealand Government, The Treasury, 2002)
This paper develops a new open economy structural VAR model of the New Zealand economy. The model adopts techniques introduced by Cushman and Zha (1997) and Dungey and Pagan (2000) to identify international and domestic shocks and dynamic responses to these shocks in a small open economy. The international variables are block exogenous and the model includes restrictions on contemporaneous and lagged variables. Novel features include the introduction of an expanded set of domestic financial variables not captured in previous New Zealand VAR models, the use of a forward looking Taylor Rule to identify monetary policy, and the introduction of a climate variable to capture the impact of climatic conditions on the business cycle. Key results to emerge are the significant influence of international variables on the New Zealand business cycle, the importance of separately identifying import price and export price shocks, and the significant influence of climate.
Keywords: C22; E32; E44; F41; 330; Open economy; structural VAR models; business cycles; climate; commodity prices; international linkages; financial conditions.